1992
DOI: 10.1002/bjs.1800790209
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modulation of haematoporphyrin derivative photodynamic therapy on colorectal carcinoma multicellular spheroids by verapamil

Abstract: Photodynamic therapy has possible applications in the treatment of colorectal carcinoma. The photosensitizer haematoporphyrin derivative (HpD) is selectively retained by tumours. Agents which block p-glycoprotein, an export protein expressed to increased levels in a high proportion of colorectal carcinomas, may modulate photodynamic therapy by reducing HpD efflux from cells. Multicellular spheroids derived from the colorectal cell lines HRT18 and HT29 were incubated for 24 h with 1 microgram ml-1 HpD and 0, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the last decade, several authors studied the photodynamic effects in MDR cells in culture, with promising results. Initially, it was shown that there was no difference in Photofrin accumulation or photosensitization between sensitive and MDR Friend leukemia cell lines [3], although the accumulation of the hematoporphyrin derivative was lower in multicellular spheroids derived from a human colorectal carcinoma cell line, a kind of tumor that usually overexpresses Pgp [39,40].…”
Section: Pdt Of Mdr Tumor Cellsmentioning
confidence: 99%
“…In the last decade, several authors studied the photodynamic effects in MDR cells in culture, with promising results. Initially, it was shown that there was no difference in Photofrin accumulation or photosensitization between sensitive and MDR Friend leukemia cell lines [3], although the accumulation of the hematoporphyrin derivative was lower in multicellular spheroids derived from a human colorectal carcinoma cell line, a kind of tumor that usually overexpresses Pgp [39,40].…”
Section: Pdt Of Mdr Tumor Cellsmentioning
confidence: 99%
“…An interesting study exploring the interaction of haematoporphyrin derivative (HpD) with verapamil, a calcium channel blocker, observed that the small molecule improved the overall efficacy of PDT in colorectal cancer spheroids. This beneficial interaction was hypothesized to arise from verapamil's ability to hamper cellular efflux pumps, thus increasing intracellular concentrations of the photosensitizer [43].…”
Section: Screening For Combination Regimensmentioning
confidence: 99%
“…This, and other early studies, focused mainly on evaluating hematoporphyrin (Hpd) distributions and the effects of Hpd-PDT in a variety of MCS models [15][16][17][18][19]. In particular, fundamental studies by West [16] and West et al [19] demonstrated that human colon carcinoma spheroids were more resistant to Hpd-PDT compared to monolayers and that the sensitivity to PDT decreased with increasing spheroid size.…”
Section: Mcs In Basic Pdt Studiesmentioning
confidence: 99%